Justice by Luck: How Unclear Records Force Some Unlucky Prisoners to Serve Unconstitutional Sentences in the Wake of Johnson v. United States - Nicholas C. Coyle (Washington University Law Review, 2020)
The Armed Career Criminal Act (ACCA) imposes mandatory minimum sentences on individuals convicted of being a felon in possession of a firearm who have at least three prior convictions for “violent felon[ies].” “Violent felon[ies]” include those crimes contemplated by the ACCA’s “residual clause.” The Supreme Court ruled that the residual clause was unconstitutional in Johnson v. United States in 2015. As the decision in Johnson was retroactive, individuals whose sentences were enhanced on the basis of the residual clause may seek relief under Johnson. In affording such relief, however, the circuits disagree as to what standard of proof should apply to the question of whether a sentence enhancement was in fact based on the residual clause. Some circuits have held that a movant must show only that his sentence enhancement “may have” been based on the residual clause in order to have the sentence vacated. Other circuits, however, have held that a movant must meet the higher preponderance-of-the-evidence standard by showing that the judge more than likely relied on the residual clause in handing down the sentence. In 2019, the Fifth Circuit in United States v. Clay chose sides in the circuit split by adopting the harsher preponderance-of-the-evidence standard. This Note uses the Fifth Circuit’s decision in Clay as a springboard for analyzing the consequences of the preponderance-of-the evidence standard.
Keywords: Criminal law; Armed Career Criminals Act; ACCA; Johnson v. United States 135 S. Ct. 2551 (2015); United States v. Clay 921 F.3d 550 (5th Cir. 2019)